A Olimpíada Mato-grossense de Química e as TIC : melhorando o rendimento escolar - Martins, Vagner José (2018)
One of the major challenges faced by educators is to bring meaning of science to students. Students are becoming increasingly less interested in the traditional model of teaching and the result is reflected in the low learning index. The contextualization and technology combined with the execution of projects related to everyday issues has proved efficient to optimize the construction of student learning. The Scientific Olympiads are intellectual events aimed at students of various fields of knowledge, who help in the popularization of Science. These events are increasingly popular in Brazil, and students are increasingly interested in attending. In this work, we analyzed how the Mato Grosso Chemistry Olympiad allied to Information and Communication Technologies can help to improve school performance. The work was developed in three steps. At each stage the students had access to various digital media and were evaluated from online tests. The objective of the present study was to verify if participation in the Mato Grosso Chemistry Olympiad, through access to a specific site and social networks (Facebook and WhatsApp) can contribute to the improvement of the academic performance of thirty third-grade students of Hi-School of a Public School in Rondonópolis-MT. The site quimicaolimpíca.net has videos, handouts, exercise lists and online simulations that allow students to evaluate in real time.The results obtained indicated that the media offered by the site and the socialization in the groups formed in the social networks optimized the academic performance of the participants of the research.